2018
DOI: 10.1039/c8ra03505a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the spontaneous formation of hybrid PdOx/PEDOT films: electroless deposition and oxygen reduction activity

Abstract: Hybrid palladium oxide/poly (3,4-ethylenedioxythiophene)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this regard, a wide variety of materials have been reported to decrease the ORR onset potential or enhance the 4electron mechanism when integrated to PEDOT-based electrodes, including CoMn 2 O 4 spinel nanorods, 41 reduced graphene oxide with Fe 3 O 4 nanorods 42 and Au nanoparticles, 43 graphene quantum dots, 44 hemin, 45 MnO x , 46 and PdO x. 47 Even, the integration of electrochemically inactive materials such as PEG-PDMS-PEG block copolymers within the PEDOT matrix has been reported to improve the ORR by modifying the conducting polymer structure and, thus, its electrocatalytic activity. 48 These kinds of strategies operate on the redox reaction mechanism of the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a wide variety of materials have been reported to decrease the ORR onset potential or enhance the 4electron mechanism when integrated to PEDOT-based electrodes, including CoMn 2 O 4 spinel nanorods, 41 reduced graphene oxide with Fe 3 O 4 nanorods 42 and Au nanoparticles, 43 graphene quantum dots, 44 hemin, 45 MnO x , 46 and PdO x. 47 Even, the integration of electrochemically inactive materials such as PEG-PDMS-PEG block copolymers within the PEDOT matrix has been reported to improve the ORR by modifying the conducting polymer structure and, thus, its electrocatalytic activity. 48 These kinds of strategies operate on the redox reaction mechanism of the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…Several conducting polymers have been investigated as effective metal-free electrocatalysts for the ORR, including polypyrrole (PPy), , polyaniline (PANI), , and poly­(3,4-ethylenedioxythiophene) (PEDOT). , These polymers act not only as efficient ORR electrocatalysts but also as conductive supports (replacing the typically used carbon), as binders (replacing Nafion, the most commonly used material that accounts for almost 40% of the cost of the reaction cell), and as precursors for pyrolyzed M-N x /C catalysts. PEDOT has received the most interest ever since Winther-Jensen observed its ability to catalyze the ORR . PEDOT is also used in many other electrochemical applications, including sensors, solar cells, organic light-emitting diodes, supercapacitors, and Li-ion batteries , because of its low cost, high electronic conductivity, good capacitive behavior, distinct redox properties, mechanical flexibility, and high chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…A high value of n leads to the production of H 2 O as the only byproduct (according to eq ) without any H 2 O 2 , thereby protecting the PEMFC from deterioration. The literature suggests that the ORR at a PEDOT surface proceeds through the two overall pathways (i) and (ii), depending upon several factors, including the polymerization method (electro-, chemical-, or vapor-phase polymerization), morphology, synthesis solvent, and presence of metal oxides. , ,,, For example, Abdelhamid et al revealed that the ORR proceeds through the two-electron or mixed reduction pathway in an alkaline electrolyte at PEDOT [polymerized from the ionic liquid 1-butyl-1-methylpyrrolidinium bis­(trifluoromethylsulfonyl)­imide (C4mpyrTFSI)] in a sandwich configuration on flexible carbon cloth electrodes ( n = 2.7) . Shi et al reported that the ORR proceeds through the two-electron pathway at PEDOT:PSS ( n = 2.0–2.2) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations